Zircon inheritance, sources of Devonian granitic magmas and crustal structure in central Victoria. Issue 2 (17th February 2023) - Clemens, J. D.; Stevens, G.; Coetzer, L. M.
Abstract: In central Victoria, inherited zircon in Devonian igneous rocks and detrital zircon in metasedimentary country rocks and an amphibolite-facies xenolith show that Mesoproterozoic parts of the underlying Selwyn Block cannot be the source for all the silicic magmas. Zircon inheritance in S-type samples reveals significant thermal events at 525–425 Ma and 1200–1100 Ma. Both S- and I-type samples have prominent zircon age peaks at 420–410 Ma, which record high-grade metamorphism of the deep crust during the terminal phases of the Benambran and Bindian orogenies. All I-type rocks have 650–500 Ma peaks, suggesting derivation from an arc-related metavolcanic source in the upper Selwyn Block. Protoliths of the greenschist-facies Ordovician metasediments and the amphibolite-facies Cambrian metasedimentary xenolith were deposited in distal backarc settings. Most inherited zircon cores are metamorphic, and the strongest zircon inheritance occurs in hornblende-bearing I-type rocks, highlighting their largely crustal origin. Zircon populations at ca 1400 Ma, thought to signal sediment derivation from East Antarctica and Rodinia-Nuna, are mostly absent in I-type samples and some S-types. The ca 1400 Ma signal probably applies to the upper, metasedimentary Selwyn Block, so Devonian S-type magmas were sourced mainly in the deeper sections. Zircon inheritance in the Devonian igneous rocks was not influenced by the exposed metasedimentary country rocks. Two samples from one of the smaller plutons have contrasting patterns of zircon inheritance, suggesting relatively small-scale source heterogeneity. Many rounded and corroded cores in zircon crystals yield the same ages as the crystallisation dates for the rocks, and thus are antecrysts. Higher whole-rock Zr contents generally correlate with higher proportions of inherited zircon, and differentiation does not affect this relationship. The degree of partial melting of a magma source and the efficiency of crystal entrainment are critical in governing zircon inheritance. KEY POINTS: Mesoproterozoic sections of the Selwyn Block cannot be the sources for all the Devonian silicic magmas in central Victoria. I-type rocks have 650–500 Ma zircon age peaks, suggesting derivation from arc-related metavolcanic rocks in the upper Selwyn Block. Hornblende-bearing I-type rocks have the strongest zircon inheritance patterns, indicating the largely crustal origins of I-type magmas. Exposed metasedimentary country rocks were not involved in magma genesis.